Rethinking Value-added Tax Policy on Domestic Wastewater Treatment Services in Indonesia - Murwendah, Murwendah; Rosdiana, Haula; Inayati, Inayati; Iraman, Endra (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
The provision of wastewater treatment services is crucial for protecting human health and maintaining clean water availability. This goal is also a key priority in the Sustainable Development Goals (SDGs). However, the wastewater treatment sector in Indonesia is subject to Value-Added Tax (VAT), resulting in higher expenses for wastewater services, including the costs associated with tax collection. Excessive taxation, including VAT, might decrease the availability of domestic wastewater treatment services from the producers' side and restrict consumers' access to these services. Instead, tax policy should provide incentives for domestic wastewater services aiming to promote development. This study examines the adoption of a VAT policy for domestic wastewater treatment services in Indonesia, emphasising its effects on affordability and sustainability in domestic wastewater management and its policy alternatives. This study employs a qualitative approach. Field observations with in-depth interviews and Focus Group Discussions were conducted in several domestic wastewater treatment sites in DKI Jakarta, Medan, and Surakarta. These field observations were conducted to collect data and information about the business processes in the industries and taxation aspects, especially VAT that affects the industries. The results indicate that providing VAT facilities is crucial for advancing the SDGs program. The VAT facilities policy will result in more significant advantages for the government and society than the revenue forgone from the facilities. This study suggests that developing a policy regarding VAT facilities is essential for domestic wastewater treatment systems. The facilities should apply to services provided by local governments or private entities in collaboration with the government. This VAT incentive proposal is simplified due to its compliance with Article 4A paragraph (3) letter (m) of VAT Law No. 42 of 2009, recently amended by Law No. 7 of 2021. While this study has provided insights into the current situation, further studies need to be conducted to investigate VAT facilities' impact on producers and consumers in the wastewater treatment sector, including the multiplier effects of providing VAT incentives.